2019
DOI: 10.1002/pros.23865
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory retrospective multicenter study of prognostic factors in mCRPC patients undergoing enzalutamide treatment: Focus on early PSA decline and kinetics at time of progression

Abstract: Background Recent studies have shown that an early prostate‐specific antigen (PSA) response to androgen receptor‐targeting agents in metastatic castration‐resistant prostate cancer (mCRPC) is associated with a better prognosis. We analyzed the early PSA response to enzalutamide (ENZ) by measuring the PSA doubling time (PSADT) and PSA velocity (PSAV) while monitoring oncologic outcomes and survival in Japanese patients. Methods We analyzed a total of 241 patients with mCRPC who were treated with ENZ. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…In this study, the multivariate analysis revealed that the time to CRPC within 12 months was the independent predictive factor for poorer PSA-PFS. This finding was consistent with those of previous reports [5,18,19].…”
Section: Plos Onesupporting
confidence: 94%
“…In this study, the multivariate analysis revealed that the time to CRPC within 12 months was the independent predictive factor for poorer PSA-PFS. This finding was consistent with those of previous reports [5,18,19].…”
Section: Plos Onesupporting
confidence: 94%
“…In this study, the multivariate analysis revealed that the time to CRPC within 12months was the independent predictive factor for worse PSA PFS, and lower PSA response to enzalutamide treatment was an independent predictive factor for worse OS. These ndings were consistent with those of previous reports (5,16,17), and suggested that enzalutamide might show strong effects if it was administrated at the early phase of CRPC treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Multivariable analysis showed that the plasma level of miR-21 (but not miR-223 or miR-141) was associated with outcome (OS and PFS), independently of other clinical variables. In our evaluation of different clinical parameters usually included in prognostic/predictive models of metastatic prostate cancer (36) time to development of castration resistance and Hb levels were confirmed as independent prognostic factors for OS, findings in line with the results of previous studies of mCRPC patients treated with enzalutamide (37). Interestingly, low Hb levels are also associated with poor survival in several other tumor types (38).…”
Section: Discussionsupporting
confidence: 88%